2007
DOI: 10.1365/s10337-007-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Chromatographic Behavior of Epirubicin and its Analogues on High Purity Silica Using Reversed-Phase Solvents

Abstract: The influence of temperature on the retention behavior of epirubicin and its analogues on high purity silica with reversed-phase solvents has been systematically investigated. It was found that temperature effects on retention are highly dependent on the type and concentration of organic modifier, as well as the pH of the mobile phase. In organic-rich mobile phases, the type of organic modifier plays an important role. With an aprotic solvent as modifier, retention times show anomalous increases with elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 26 publications
2
11
0
4
Order By: Relevance
“…It is known that column temperature has an important influence on the separation under HILIC conditions [36,44,47]. In our study with the increase of column temperature, a decrease in the retention time was observed for all compounds, except for trimesic acid (Fig.…”
Section: Influence Of Column Temperature On the Hilic Retentionsupporting
confidence: 51%
“…It is known that column temperature has an important influence on the separation under HILIC conditions [36,44,47]. In our study with the increase of column temperature, a decrease in the retention time was observed for all compounds, except for trimesic acid (Fig.…”
Section: Influence Of Column Temperature On the Hilic Retentionsupporting
confidence: 51%
“…These interactions may add adsorptive contributions also to the overall HILIC retention 17, 19, and from the results presented in the previous sections, it can be supposed that adsorption occurred in experiments conducted here. In RP‐HPLC stationary phases made of high‐purity silica, the degree of ionization of silanols increases with increasing pH of the mobile phase 26, 33, and this was observed in a bare silica phase with high ACN% too, at least within a mobile‐phase pH interval from 2.9 to 5.2 55. The TSKgel Amide‐80 column is based on silica, the silanols of which are reported to provide some ion‐exchange interaction with charged analytes 20, 23, 41.…”
Section: Resultsmentioning
confidence: 97%
“…As far as the role of ACN at different pH values is concerned, some authors provided an explanation of analogous findings, although in a different application. According to 55, by modulation of the mobile‐phase pH, the mechanism governing retention of the solutes can pass from hydrophilic to the ion‐exchange interaction. Such interaction is strengthened by a low water% because the ions present in the mobile phase have poor solubility in ACN and thus are strongly retained into the thin aqueous layer adsorbed onto the stationary phase surface.…”
Section: Resultsmentioning
confidence: 99%
“…Column temperature is an important factor in HILIC separations [27][28][29] as it influences significantly on the following properties: (i) diffusivity of the analytes; (ii) viscosity of the MP, which is closely correlated with hydrophobicity and hydrophilicity of the MP; (iii) enthalpy and entropy change of the analytes in the transferring process from the MP to SP; (iv) pKa of the analytes and pH of the MP [30][31][32]. An increasing number of reports [18][19][20]25,[27][28][29]31,[33][34][35][36][37] on thermodynamics in HILIC were found in recent years, which provided necessary theory guidance when column temperature was used as a variant regulating selectivity and analysis speed.…”
Section: Effect Of Column Temperaturementioning
confidence: 99%